FAKTOR YANG MEMPENGARUHI FINANCIAL PERFOMANCE PADA FAMILY BUSINESS PROPERTY AND REAL ESTATE - Danny, Mario Gho; Cahyadi, Hadi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to test empirically the effect of good corporate governance and capital structure in family business in property and real estate companies listed on the Indonesia Stock Exchange for the period 2017 - 2020. This study uses data from 14 family business in property and real estate companies that have been selected using the purposive sampling method. with a total of 56 data for four years. The data used are secondary data in the form of financial reports. This research data processing using the program SPSS version 24. The results showed that the family ownership, family involvement in bod and capital structure were negative and not significant effect on financial performance, family involvement in boc has a positive and significant effect on financial performance. The implication of this research is the involvement of commissioner in supervision is the main key for the future of the company, how the commisioner need to oversees the actions or decisions of the directors. The existence of supervision from the commissioners is able to create a good influence on the company’s financial performance on decisions made by the directors.